European experience of patients with HER2-positive advanced/metastatic breast cancer accessing trastuzumab deruxtecan through a named patient program: the EUROPA T-DXd study - Saura, Cristina; Wildiers, Hans; Bianchini, Giampaolo; García-Saenz, José Ángel; Allignol, Arthur; Logue, Amanda; Lucerna, Markus; Stamenitis, Sabine; De Laurentiis, Michelino (Frontiers in Oncology, 2025)
IntroductionIn January 2021, trastuzumab deruxtecan (T-DXd) received conditional approval in the European Union for the treatment of human epidermal growth factor receptor 2–positive (HER2-positive) unresectable or metastatic breast cancer in patients who had previously received two or more prior anti-HER2–based regimens. In March 2021, a named patient program (NPP) was initiated to enable eligible patients to access T-DXd when not yet locally available. This European, multicenter, multinational, observational, single-arm data collection study included heavily pretreated patients with HER2-positive metastatic breast cancer who received T-DXd under the NPP and was intended to generate real-world insights from routine clinical practice.MethodsPatients with unresectable or metastatic HER2-positive breast cancer who had received ≥2 prior anti-HER2–based regimens and were treated with T-DXd (5.4 mg/kg) under the NPP (DS8201-0002-EAP-MA) were eligible for inclusion in the study. Participation in the data collection was optional and independent of eligibility for the NPP. The primary endpoint was real-world time to treatment discontinuation. Secondary endpoints included real-world progression-free survival, prior HER2-targeted treatment patterns, reasons for T-DXd treatment discontinuation, safety, and antiemetic prophylaxis prior to T-DXd initiation. Adverse events were collected via a pharmacovigilance system.ResultsIn total, 256 patients (from centers across Ireland, Italy, and Spain) participated in the study. At data cutoff (March 28, 2024), 243 patients (94.9%) had discontinued treatment. The primary endpoint of median (95% confidence interval [CI]) real-world time to treatment discontinuation was 13.0 (11.2, 15.2) months. Median (95% CI) real-world progression-free survival was 15.2 (11.9, 17.3) months. The median number (range) of prior anti-HER2 lines of therapy in the metastatic setting was 3 (0–6). The main reason for T-DXd treatment discontinuation was disease progression (46.1%). Use of an antiemetic regimen with prophylactic intent was reported in 80.9% of patients. No new safety signals were identified.ConclusionResults from this real-world study are consistent with the clinical benefit observed with T-DXd in patients with HER2-positive metastatic breast cancer in phase II/III clinical trials in the third-line setting and beyond.Clinical trial registrationhttps://clinicaltrials.gov/study/NCT05458401; identifier NCT05458401